Optimization of the Implementation of Notary Responsibilities in Providing Social Services to Underprivate Communities in Kendal Regency - Tria Agustina, Histy; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze the optimal implementation of notaries' responsibilities in providing social services to underprivileged communities in Kendal Regency and to identify obstacles and solutions encountered in its implementation. The study used an empirical juridical method with a statutory regulatory approach, literature study, and interviews with two notaries in Kendal Regency. The results of the study indicate that the obligation of notaries to provide free legal services to underprivileged communities is regulated in the Notary Law, the Notary Code of Ethics, and the principle of justice in the 1945 Constitution. However, its implementation is highly dependent on the notary's personal awareness due to the lack of standard guidelines regarding the mechanism for determining the criteria for underprivileged communities or the procedures for providing free services. The notaries interviewed stated that the provision of social services is carried out on the basis of humanity and professional integrity, not due to pressure from normative sanctions. The main obstacles faced include relatively high operational costs, the lack of standards for verifying clients' economic capabilities, and the risk of abuse by those who are actually well-off. The proposed solutions include the development of technical guidelines by professional organizations, increased socialization, and strengthening the integrity of notaries as public officials.